A note on an iterative least squares estimation method for ARMA and VARMA models - George Kapetanios (Queen Mary University of London, Department of Economics, 2002)
In this note we suggest a new iterative least squares method for estimating scalar and vector ARMA models. A Monte Carlo study shows that the method has better small sample properties than existing least squares methods and compares favourably with maximum likelihood estimation as well.
Keywords: C13; C22; 330; ARMA models; Theorie; ARMA-Modell